PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA SUB SEKTOR LOGAM YANG TERDAFTAR DI BEI PADA PERIODE 2019-2022 - Irvan Alfredo Pardosi; Ronny Buha Sihotang; Remista Simbolon (POLITEKNIK LP3I JAKARTA, 2024)
Legal efforts made by companies to avoid taxes by reducing the deferred tax burden are called tax avoidance. If tax avoidance activities are carried out according to the rules of the applicable law, it is considered legal by the company. The purpose of this study is to understand and analyze the various benefits of profitability (X1) and business growth (X2) on financial performance (Y) in the Metal Subsector listed on the Indonesia Stock Exchange. The method used in this research is quantitative, and the annual report of the Metal Company for the period 2019-2022 as secondary data. Panel data regression is applied for analysis techniques. The findings of this study explain that profitability produced with ROA and company size produced with SIZE have no significant effect on Tax Avoidance in Metal Companies on the Indonesia Stock Exchange. Keywords: Profitability, Company Size, Tax Avoidance